2014
DOI: 10.1590/s1980-57642014dn83000012
|View full text |Cite
|
Sign up to set email alerts
|

Discourse intervention strategies in Alzheimer's disease: Eye-tracking and the effect of visual cues in conversation

Abstract: ObjectiveThe goal of this study was to investigate whether on-topic visual cues can serve as aids for the maintenance of discourse coherence and informativeness in autobiographical narratives of persons with Alzheimer's disease (AD).MethodsThe experiment consisted of three randomized conversation conditions: one without prompts, showing a blank computer screen; an on-topic condition, showing a picture and a sentence about the conversation; and an off-topic condition, showing a picture and a sentence which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Seven of the included studies analysed eye movement behaviours during static image search tasks [ 38 , 45 , 63 , 65 , 70 , 71 , 72 ]. Interestingly, based on our search, static image search tasks appear to be the most common naturalistic eye movement tasks employed when analysing eye movement behaviours in AD/MCI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven of the included studies analysed eye movement behaviours during static image search tasks [ 38 , 45 , 63 , 65 , 70 , 71 , 72 ]. Interestingly, based on our search, static image search tasks appear to be the most common naturalistic eye movement tasks employed when analysing eye movement behaviours in AD/MCI.…”
Section: Resultsmentioning
confidence: 99%
“…Brandão et al [ 63 ] analysed eye movements during free recall of an important life event whilst relevant or irrelevant visual cues (images and sentences) were presented. In doing so, Brandão et al [ 63 ] observed that HOC fixated on relevant images longer than irrelevant images, however, this effect was not observed for people with AD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attentional processes and working memory have been studied mostly using the prosaccade and antisaccade task (Crawford et al, 2015;Crawford et al, 2013;Crawford et al, 2017;Crawford & Higham, 2016), but also a variety of other tasks have been used (Brandão et al, 2014;Chau et al, 2015;Chau et al, 2016;Mapstone et al, 2001;Viskontas et al, 2011;Rösler et al, 2000), including reading (Fernández et al, 2016) and finding objects in a natural scene (Dragan et al, 2017). Given the several different cognitive domains affected in AD, ET is potentially a useful tool to further investigate cognition rather than relying only on classic paper and pencil tests.…”
Section: Alzheimer´s Diseasementioning
confidence: 99%